Non Puerperal Uterine Inversion in Unmarried Girl with Submucous Fibroid - Yasmin, Naila; Aleem, Mehmood (Annals of Punjab Medical College, 2011)
A rare case of nonpuerperal uterine inversion caused by a large fundal leiomyoma in an unmarried girl presenting with heavy irregular vaginal bleeding, feeling of mass in vagina, severe dysmenorrhoea and retention of urine. Uterine inversion wasdiagnosed by clinical examination and radiological investigations. Her inversion was corrected by Haultain procedure performed abdominally.